PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN TEKNOLOGI WIDE AREA NETWORK (WAN) KELAS XI TJKT - Saputra, Asril; Rini, Faiza; Mary, Thomson (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2023)
This research aims to develop interactive learning media that is valid and easy to use. Even though students have received education with the latest learning methods, they still experience difficulties in understanding learning concepts conveyed through conventional media. This research uses the Research and Development (RD) method by applying the ADDIE development model. The result of this research is the development of interactive learning media which has a very high level of validity, namely 92.70% in terms of media and 96.15% in terms of material. When tested in practice, this media was considered very practical based on teacher responses which reached 92.5% in the very practical category, and student responses which reached 90.62% in the very practical category.